Myocardial revascularization without cardiopulmonary bypass through a ministernotomy - Klokočovnik, Tomislav (Endoskopska revija, 2007)
Background. Although a minimally invasive operative approach has been increasingly used in cardiovascular surgery lately, minimal access off-pump revascularization remains an uncommon procedure.Patients and methods. At this Department, revascularisation of the left anterior descending artery with the left internal mammary artery (LIMA- LAD) performed via a ministernotomy without cardiopulmonary bypass (CPB), was used in two patients with a total LAD occlusion and good left ventricular function.Results. A LIMA-LAD anastomosis without CPB performed via a ministernotomy is a safe, yet technically relatively demanding operative technique. Both our patients had anuneventful postoperative course and were discharged from the hospital four and five days after the operation, respectively. No surgery-related complications were observed within 30 days of surgery. Conclusions. In properly selected patients, a LIMA-LAD off-pump anastomosis performed through a ministernotomy has proved a safe technique with good postoperative results Its advantages include decreased postoperative pain, faster recovery and shorter hospital stay.
Keywords: kardiovaskularna kirurgija; kirurško zdravljenje